Blameworthiness in Strategic Games - Naumov, Pavel; Tao, Jia (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
There are multiple notions of coalitional responsibility. The focus of this paper is on the blameworthiness defined through the principle of alternative possibilities: a coalition is blamable for a statement if the statement is true, but the coalition had a strategy to prevent it. The main technical result is a sound and complete bimodal logical system that describes properties of blameworthiness in one-shot games.